On a Cahn–Hilliard/Allen–Cahn system coupled with a type III heat equation and singular potentials. (July 2020) - Makki, Ahmad; Miranville, Alain; Saoud, Wafa
Abstract: Our aim in this article is to study the asymptotic behavior of a Cahn–Hilliard/Allen–Cahn system coupled with a heat equation based on the type III heat conduction law with singular potentials. We also show further regularity results and we prove a strict separation property (from the pure states) in one space dimension.